2020
DOI: 10.1002/ece3.6240
|View full text |Cite
|
Sign up to set email alerts
|

Detecting shrub encroachment in seminatural grasslands using UAS LiDAR

Abstract: Shrub encroachment in seminatural grasslands threatens local biodiversity unless management is applied to reduce shrub density. Dense vegetation of Cytisus scoparius homogenizes the landscape negatively affecting local plant diversity. Detecting structural change (e.g., biomass) is essential for assessing negative impacts of encroachment. Hence, exploring new monitoring tools to achieve this task is important for effectively capturing change and evaluating management activities. This study combines traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
0
7
2
2
Order By: Relevance
“…The presented method could be used to accurately identify land cover types (e.g., forest, meadow) and their sub-classes (e.g., forest types). In our case, the field validation (at 72 points) reflects 83% classification accuracy, which is higher than the accuracy of the classification made by Saarinen et al [54] or Michez et al [55], and slightly lower than obtained by Madsen et al [56].…”
Section: Methodological Suggestions For Identification and Vegetation Density Measurementscontrasting
confidence: 71%
See 2 more Smart Citations
“…The presented method could be used to accurately identify land cover types (e.g., forest, meadow) and their sub-classes (e.g., forest types). In our case, the field validation (at 72 points) reflects 83% classification accuracy, which is higher than the accuracy of the classification made by Saarinen et al [54] or Michez et al [55], and slightly lower than obtained by Madsen et al [56].…”
Section: Methodological Suggestions For Identification and Vegetation Density Measurementscontrasting
confidence: 71%
“…For example, in floodplain forests, Saarinen et al [54] achieved an accuracy of 72.6% when classifying mobile laser scanner data, while Michez et al [55] obtained an accuracy of 79.5-84.1% when classifying drone-derived point clouds. Madsen et al [56] achieved 86.9-95.2% classification accuracy when classifying aerial LiDAR data in a bushy area. The classification accuracy of open surfaces (75%) is the lowest because some vegetated plots were also defined as open surfaces.…”
Section: Poplar Plantation (Young) Native Poplar Forestmentioning
confidence: 99%
See 1 more Smart Citation
“…Hesperostipa curtesita is another dominant grass in this system ( Lamb 2008 ), yet showed a significant negative association with wolf-willow. While many studies report richness effects associated with shrub presence ( Anthelme et al 2007 ; Price and Morgan 2008 ; Ratajczak et al 2012 ; Madsen et al 2020 ), our study shows that important community changes can occur even in the absence of a richness effect. Future studies should consider incorporating architectural or abundance measures (like our wolf-willow score) as well as looking at other components of biodiversity.…”
Section: Discussioncontrasting
confidence: 71%
“…Combined with field measurements and machine learning algorithms, high-resolution (≤ 30 m) satellite imagery and aerial photographs are widely used to observe small-scale woody expansion and can obtain accurate, detailed local information, such as encroaching species and plant height (Madsen et al, 2020;Marston et al, 2017); however, the limited spatial coverage and the lack of effective upscaling methods have hindered the application in large-scale research. Yang et al (2020) found that 250-500 m resolutions were suitable for the observation of potential woody vegetation coverage in a savanna ecosystem, suggesting that medium-resolution remote sensing might help to detect where WPE is distributed globally.…”
Section: Introductionmentioning
confidence: 99%